'They're just not my team': the issue of player allegiances within Irish football, 2007–2012. (18th August 2018) - Murray, Conor; Hassan, David
Abstract : Rarely, it seems, is the interplay between sport and politics, or perhaps more accurately sport and identity, so apparent as in Ireland. Whilst there has been a considerable degree of work undertaken in examining the historiography of the indigenous sporting organization, the Gaelic Athletic Association, the level of focus on other sports in Ireland has, in comparison, been somewhat more modest. This essay considers the emergence and outworking of the player eligibility dispute between the Football Association of Ireland (FAI), as the governing body of the game in the Republic of Ireland, and the Irish Football Association, their counterparts in Northern Ireland, focussing specifically on the height of this dispute between 2007 and 2012. Drawing upon interview material from players who previously have not spoken about their personal decision to leave Northern Ireland and play for the Republic of Ireland, a combination of social, personal and political factors, combined, allow for a detailed account of this process to be established. It profiles a long-running and difficult rivalry between soccer authorities on a small island on the western seaboard of Europe but where passions remain high in both sport and politics.